Methodological approach to evaluating the DreamBox Reading Plus intervention: a cluster randomised trial - Gellen, Sandor; Ainsworth, Steph; Morris, Stephen; Lewin, Cathy; Wicker, Kate (Frontiers in Education, 2025)
BackgroundImproving reading skills in primary school pupils is a crucial focus for educators, researchers, and policymakers worldwide. Within the United Kingdom many schools are opting to use “evidence-based” reading programs to deliver or supplement the teaching of reading. This article reports a protocol for a rigorous efficacy study of DreamBox Reading Plus, an online adaptive program aimed at improving reading fluency, comprehension, and vocabulary for elementary pupils.Methods and analysisWe conduct a pragmatic, parallel cluster randomized controlled trial in English primary schools, with schools serving as the unit of randomisation. Schools are allocated to either a treatment group, which received the DreamBox Reading Plus intervention, or a control group following standard practices, on a 1:1 basis. The study’s primary outcome focuses on reading attainment, assessed using a standardized reading test for pupils starting in Year 5. Secondary outcomes include various measures of reading fluency, comprehension, vocabulary, reading self-efficacy, and motivation. The intervention is scheduled to begin in October 2024, with outcome analysis planned for August 2025.DiscussionBy generating high-quality evidence on the efficacy of DreamBox Reading Plus, this study aims to inform best practices and contribute to the broader discourse on effective educational technologies in the classroom.